Factors influencing premiums on local wines: an exploratory assessment of Kansas wine - McDonald, Jennifer (Kansas State University, 2016)
While understanding consumer decisions about food choices is complex, the nature of wines makes it even more difficult to decipher how consumers arrive at their choices. Given the perceived importance of "local", how willing are consumers to pay for locally-produced wine? And, what characteristics of the wine influence the premium that consumers pay for it? These are the two related questions that this research seeks to address. The research uses a case study approach to explore how five wine characteristics of local Kansas wine influence the premium consumers are willing to pay. The five characteristics are appearance, aroma, body, taste and finish. The study uses four pairs of wine in the following groups: sweet white, dry white, semi-sweet red and dry red. Each pair is made up of a Kansas wine and a non-Kansas wine. A very well-defined set of focus group participants were invited to taste these wine without knowing the identity of the wines and score them according to their characteristics and then provide an indication of how much they are willing to pay. The case results indicate that the focus group participants were willing to discount Kansas wines in all cases of the four pairs. The factors affecting the discount were finish for sweet white wines, appearance for sweet red wines, taste and aroma for dry white and dry red wines. The implication of this exploratory case study is that while most local residents proclaim their willingness to pay a premium for local wines, when tested against national or international competitors, consumers are unwilling to pay a premium for these local wines because the local wines lack the desired quality the international wines have. The information is important because it provides direction for an entrepreneur seeking to develop local wines to focus on understanding and addressing the characteristics which influence consumers' willingness to pay a premium even as she determines which particular wines current players in the local Kansas industry has the potential to be competitive if they address the characteristics upon which they are penalized by consumers. This, despite this being an exploratory case study, it provides important direction for entrepreneurial action.
Keywords: Consumer Preferences; Wine; Locally Grown; Premium; Willingness to Pay